Função social da propriedade urbana e o Plano Diretor - Pires, Lilian Regina Gabriel Moreira (2005)
From XIX century the concept of real state has gone through by important changes and on its structure the idea of social function was incorporated on it, compeling the landlord to use the land property not for individual advantages but, for settlers benefit as well. The 1988 Federal Constituition brought forward to devote a paragraf to urban policy. Thus, the social function of urban society started being treated as a basic right, a principle straight atached to the social concernings and financial values. Further the 10.257, law from the 10th july 2001 named the City Law regulated constitucional mechanisms. The social function was not stablished by the constitutional legislator, and each municipal district was allowed to feature the law in accordance to their interests and need. Nevertheless it was settled that, for cities with up twenty thousand inhabits, a director scheme would be the basic mean of urban policy, compeling the urban property to accamplish its social function, as long the demands expressed at the director scheme were rendered. As it can be observed the planification has won prominence and relenance. Despite the inovation, the constituition was in need of some definitions as such: minimum content, sanctions for not edition of the plan, terms for its implementation. So that, the jurirical alternatives and pratical effects about the plan, came with the City Estatute ediction. Having as support the mentioned survey, this work has a purpose: to inquire the urban property social function and the articles 39 to 42 of the City Estatute, which came to fullfil the gaps of the institute named director scheme. For all that a short historical evolution of the property, perpassing briefly by several native countries societies constitutions. Further, it was presented the concept of property and social with a focus at the social function specifically at the points about dwelling, moving working and recreation. For this we came to the conclusion that social function of state property is a duty for every cities. Even, still having the constitution as reference, there is a determination which stands out the idea that any municipal district with rather than twenty thousand inhabits must adopt and publish the director scheme, reason wich made the planification reached relevance and importance, due to the fact that the director scheme became a issue of important matter, to implement public policies, specially to the acomplishiment of the social function of urban society. Consequently the scheme the planing and the director plan, were studied under the view of the articles 39 to 42 from the city statute. At last some decisions of Judiciary Power were brought in order to show that there is a chalenge for Executive, Legislative and Judicial Power and general society to stake a claim at the principle of social function as a mean to accomplish the objectives printed in the article 3º from 1988 Federal Constituition.